Negative Emotional Energy: A Theory of the “Dark-Side” of Interaction Ritual Chains - David Boyns; Sarah Luery (Social Sciences, 2015)
Randall Collins’ theory of interaction ritual chains is widely cited, but has been subject to little theoretical elaboration. One reason for the modest expansion of the theory is the underdevelopment of the concept of emotional energy. This paper examines emotional energy, related particularly to the dynamics of negative experiences. It asks whether or not negative emotions produce emotional energies that are qualitatively distinct from their positive counterparts. The analysis begins by tracing the development of Interaction Ritual Theory, and summarizes its core propositions. Next, it moves to a conceptualization of a “valenced” emotional energy and describes both “positive” and “negative” dimensions. Six propositions outline the central dynamics of negative emotional energy. The role of groups in the formation of positive and negative emotional energy are considered, as well as how these energies are significant sources of sociological motivation.